Is Putin's popularity (still) real? A cautionary note on using list experiments to measure popularity in authoritarian regimes. Issue 3 (4th May 2023) - Frye, Timothy; Gehlbach​, Scott; Marquardt, Kyle L.; Reuter, Ora John
ABSTRACT: Opinion polls suggest that Vladimir Putin has broad support in Russia, but there are concerns that some respondents may be lying to pollsters. Using list experiments, we revisit our earlier work on support for Putin to explore his popularity between late 2020 and mid-2022. Our findings paint an ambiguous portrait. A naive interpretation of our estimates implies that Putin was 10 to 20 percentage points less popular than opinion polls suggest. However, results from placebo experiments demonstrate that these estimates are likely subject to artificial deflation – a design effect that produces downward bias in estimates from list experiments. Although we cannot be definitive, on balance our results are consistent with the conclusion that Putin is roughly as popular as opinion polls suggest. Methodologically, our research highlights artificial deflation as a key limitation of list experiments and the importance of placebo lists as a tool to diagnose this problem.